The prolyl oligopeptidase inhibitor KYP‑2047 is not readily bioavailable to bloodstream form trypanosomes and human myelocytic leukemia cells (Journal of Pharmaceutical Negative Results, 2015)
Introduction: Only three drugs are currently available for treatment of the neurologicalstage of human African sleeping sickness caused by the protozoan parasite Trypanosomabrucei. As these drugs have serious side effects and are difficult to administer, new andsafe antitrypanosomal medications are urgently required. Research in recent years hasshown that prolyl oligopeptidase (POP) inhibitors are promising trypanocidal agents.As the novel POP inhibitor KYP‑2047 can cross the blood‑brain barrier, we aimed totest whether this compound would prove to be a promising anti‑trypanosomal drugcandidate. Materials and Methods: The efficacy of KYP‑2047 to inhibit trypanosomeand human POP was evaluated with cell lysates using the fluorogenic peptide substrateSuc‑Gly‑Pro‑Leu‑Gly‑Pro‑AMC. The trypanocidal and cytotoxic activity of KYP‑2047was studied in vitro using bloodstream forms of T. brucei and human myelocyticleukemia HL‑60 cells. The bioavailability of KYP‑2047 to T. brucei and HL‑60 cells wasdetermined by incubation of cells with the inhibitor for 24 h, followed by measuring theresidual POP activity. Results: KYP‑2047 inactivated POP in cell lysates of T. brucei andHL‑60 cells with IC50 values in the mid nanomolar range indicating that the compoundis a very potent inhibitor of the trypanosome and human enzyme. However, KYP‑2047did not affect the growth of T. brucei and HL‑60 cells. Upon incubation of the cellswith 100 μM KYP‑2047, POP activity was inhibited between 20% and 80% which istoo low to have any effect on cell growth. Conclusion: The absence of trypanocidaland cytotoxic activity of KYP‑2047 is due to low bioavailability of the inhibitor tobloodstream forms of T. brucei and human HL‑60 cells.